Confirmación molecular de especie en especímenes Anopheles recolectados en el corregimiento de Juan José, Puerto Libertador, Córdoba, Colombia (2010)
ABSTRACT: Difficulty in the morphological identification of females of various species on the Nyssorhynchus subgenus has been documented; it is due to interspecies morphological similarity, intraspecific variation and the existence of cryptic species. For this reason, molecular techniques such as PCR-RFLPITS2 has been used, they allow confirming species assignation in endemic areas. Objective To confirm the species assignation of mosquitoes Anopheles collected in Juan Jose locality, municipality of Puerto Libertador, Cordoba, as a contribution to a species inventory in the locality. Materials and methods Of 2.070 specimens identified by morphological characters, 513 (24.8%) were molecularly confirmed by PCR-RFLP-ITS2. Results The species defined by morphology as present in Juan José were: Anopheles (Nyssorhynchus) nuneztovari s.l. Gabaldon (97.44%), A. (Nys.) darlingi Root (0.77%) y A. (Nys.) oswaldoi s.l. Peryassu (0.10%). The rest of specimens (1.69%) were defined as belonging to one of the species of the Oswaldoi group. Molecular confirmation helped to determine the presence of only two species among the analyzed specimens, 99.23% A. (Nys.) nuneztovari and 0.77% A. (Nys.) darlingi. Conclusions The two species of Anopheles found in Juan Jose, during the sampling period are considered primary vectors in Colombia; this information is important to guide vector control efforts. Additionally, the results reaffirm previous reports on the difficulty of identifying A. nuneztovari s.l. by morphology and the importance of using molecular tests for species confirmation.